An Attack on Inclusive Education in Secondary Education. Limitations in Initial Teacher Training in Spain - Manuel López-Torrijo; Santiago Mengual-Andrés (Springer, 2015)
Inclusive education is hard to implement in secondary schools. Probably, one of the determining factors lies in teachers' initial  training that determines their attitude, identity and professional practice. This research analyses the initial teacher education programmes for Secondary Education, Higher Secondary Education, called bachillerato in Spain, and Vocational and Artistic training in the five best valued Spanish universities in the education field, according to the ranking I-UGR, after the European convergence process in the European Higher Education Area. The study analyses the national regulations that govern this training. A quantitative study was conducted to examine the number of credits dedicated to inclusive education and also a review of the contents of these subjects was carried out. The study concludes that this initial teacher training provides sufficient theoretical basis regarding the conceptualization of inclusive education and the skills to deal with the tutorship and academic and professional orientation. However, important limitations in training prevent future teachers from identifying students' and context's special educational needs, and the attention to diversity through different methods and curriculum adaptations.